Morphological features of fruits and seeds of Saposhnikovia divaricata (Apiaceae) - Yugrina Polina (EDP Sciences, 2021)
The article presents the characteristics of the fruits and seeds of the medicinal plant Saposhnikovia divaricata (Turcz.) Schischk.), obtained from natural habitats and under conditions of introduction. Heterocarpy has been established, which is expressed in the difference in color, the surface of the mericarp, the size of the mericarp and the seed. The size of the embryo differs slightly. The coefficient of variation of signs is from 9 to 22 %, regardless of the place of origin of the fruits.